Astroinformatics: The Importance of Mining Astronomical Data in Binary Stars Catalogues - Abushattal, A. A.; Alrawashdeh, A. A; Kraishan, A. F.
The field of Astroinformatics offers exciting new perspectives on astronomical discovery through the implementation of advanced data mining procedures. Data deluges transform research practices and methodologies across various scientific disciplines, including day-to-day astronomical research. It is essential to use innovative algorithms and methods to process astronomical data and its variety. Descriptive Data Mining was used in this study to clarify the importance and effectiveness of obtaining common data between three binary star catalogs. These catalogues are The Ninth Catalogue of Spectroscopic Binary Orbits (SB9), The Sixth Catalog of Orbits of Visual Binary Stars (6COVBS), and The Fourth Catalog of Interferometry Measurements of Binary Stars (4CIMBS). We collect scattered data from the Ninth Catalog in its latest edition in 2021, which contains astronomical information for approximately 4021 binary systems. Then we search for the orbits of these binary systems in the 6COVBS to calculate the physical and the orbital properties with high accuracy. After that, we use the 4CIMBS to look for new observations of these stars in 66,225 resolved stars in its latest edition 2020 to calculate new orbits. As a result of this research, we have found about 600 standard systems among these catalogues, which are valuable data to calculate many physical properties of such binary stars, starting from individual masses, by the combination of the spectroscopic orbital solution with the visual orbital solutions. Furthermore, calculate the orbital parallax for each system with high accuracy compared with those from space missions such as Gaia and Hipparcos give us a new and essential method to verify the validity of the data from those satellites.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture